1982
DOI: 10.1073/pnas.79.10.3325
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3: short- and long-term effects on bone and calcium metabolism in patients with postmenopausal osteoporosis.

Abstract: We evaluated the effects of therapy with a small dose (0.5 Iug/day) of 1,25-dihydroxyvitamin D3 in 12 previously untreated patients with postmenopausal osteoporosis. Combined radiocalcium kinetic and balance studies showed that at base line, net calcium absorption (mean ± SEM) was low (7 + 3%), calcium balance was negative (-59 ± 22 mg/day), and bone resorption rate (297 ± 40 mg/day) exceeded bone formation rate (239 ± 36 mg/day). After short-term therapy (6-8 months), calcium absorption was normal (27 ± 3%, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(52 citation statements)
references
References 32 publications
2
48
0
2
Order By: Relevance
“…Senile osteoporosis traditionally has been attributed to bone cell senescence and, thus, has been considered not to be amenable to therapy. We have documented a potentially treatable (28) abnormality of vitamin D metabolism, which could contribute to age-related bone loss. It is now appropriate to determine whether impaired calcium absorption in elderly women can be corrected by treatment with a small dose of 1,25(0H)2D and, if so, whether this reduces their bone loss.…”
Section: Resultsmentioning
confidence: 99%
“…Senile osteoporosis traditionally has been attributed to bone cell senescence and, thus, has been considered not to be amenable to therapy. We have documented a potentially treatable (28) abnormality of vitamin D metabolism, which could contribute to age-related bone loss. It is now appropriate to determine whether impaired calcium absorption in elderly women can be corrected by treatment with a small dose of 1,25(0H)2D and, if so, whether this reduces their bone loss.…”
Section: Resultsmentioning
confidence: 99%
“…1a (OH)D3 has been reported to prevent bone loss and increase the mechanical properties in ovariectomized rats, although its mechanism is still controversial (30 -32). 1a (OH)D3 as well as 1,25(OH) 2 D 3 increases bone mass possibly by up-regulating the intestinal absorption of calcium or modulating bone turnover (33).…”
mentioning
confidence: 99%
“…These results may indicate that 1a(OH)D3 has a suppressive effect on In earlier studies, a decrease in excretion following active vitamin D analogue was reported [6][7][8][9][10]. In ovariectomized animals, the inhibitory effect of 1, 25 (OH)2D3 on bone resorption has been demonstrated [3,4].…”
Section: Discussionmentioning
confidence: 71%
“…Taking into account the fact that the loss of L2-4 BMD measured by DXA was as much as 8% per year as demonstrated in the control group of the preventive trial, L2-4 BMD measured by DXA is a good endpoint for the evaluation of the agent in early menopausal subjects. The endpoints used in other studies in the literature are L2.4 BMD as measured by dual photon absorptiometry [6][7][8]12] and the incidence of fractures [7,8,12,13]. The percent change in these parameters was not more than 5% in one year, because the subjects studied were more than 60 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation